Motivasi Pendidikan Perspektif Hadits - M. Imamuddin; Hadini Hadini; Isnaniah Isnaniah; Fitri Alrasi (KOLONI, 2023)
Educational motivation is the driving force of a person in obtaining education. This research is a literature review. The purpose of this research is to examine educational motivation from the hadith perspective. Data sources were obtained from various books and articles both online and offline. Data analysis is done in depth. The results of this research include: motivation in Islam is known as al niiyat (intention). Indeed, every deed depends on its intention, and for each person what he intends. Educational motivation is defined as the intention or desire of adults / educators consciously in educating the physical and spiritual development of the educated towards the formation or to have balanced knowledge and personality. Whoever seeks knowledge by setting good intentions, Allah will facilitate his path to heaven. Expecting knowledge that is beneficial both for himself and the people will bring him to the pleasure of the world and the hereafter.